Music Theory as Productivity - Krims, Adam (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2000)
The author here proposes Julia Kristeva's notion of "productivity" as a way of conceiving of the relations between different theories of music. By such a notion, rather than confirming, disconfirming, or exemplifying a theory, a particular musical work (or works) may redistribute the theory. The redistribution, in fact, might not only modify the initial theory—something certainly not original to productivity—but may also bring it into articulation with fundamentally opposed models of musical function, without which, nevertheless, the original theory remains incomplete. An extended example is adduced from Schubert's Schubert's Impromptu in G-flat Major, D. 899, in connection with, first, Schenker's Free Composition (Der freie Satz), and second, Schoenberg's Theory of Harmony (Harmonielehre); Schenker's inconsistent practice with respect to first-order neighbours, along with certain issues in the Impromptu, become the occasion for examining a case of productivity.